2018
DOI: 10.9778/cmajo.20170088
|View full text |Cite
|
Sign up to set email alerts
|

Most medical practices are not parachutes: a citation analysis of practices felt by biomedical authors to be analogous to parachutes

Abstract: Background:In a 2003 paper in BMJ, the authors made the tongue-in-cheek observation that there are no randomized controlled trials (RCTs) of parachutes. This paper has been widely read, cited and used to argue that RCTs are impractical or unnecessary for some medical practices. We performed a study to identify and evaluate claims that a medical practice is akin to a parachute. Methods:Using Google Scholar, we identified all citations to the 2003 paper. We searched for claims that a specific practice was akin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 77 publications
1
20
0
Order By: Relevance
“…Critics of the PARACHUTE trial are likely to make the argument that even the most efficacious of treatments can be shown to have no effect in a randomized trial if individuals who would derive the greatest benefit selectively decline participation. The critics will claim that although few medical treatments are likely to be as effective as parachutes,15 the exclusion of selected patients could result in null trial results, whether or not the intervention being evaluated was truly effective. The critics might further argue that although randomized controlled trials are the gold standard for evaluating treatments, their results are not always guaranteed to be relevant for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Critics of the PARACHUTE trial are likely to make the argument that even the most efficacious of treatments can be shown to have no effect in a randomized trial if individuals who would derive the greatest benefit selectively decline participation. The critics will claim that although few medical treatments are likely to be as effective as parachutes,15 the exclusion of selected patients could result in null trial results, whether or not the intervention being evaluated was truly effective. The critics might further argue that although randomized controlled trials are the gold standard for evaluating treatments, their results are not always guaranteed to be relevant for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has been used to argue that RCTs are sometimes impractical or unnecessary. Nevertheless, Hayes et al [28] found that few studies have compared actual medical practices to the equivalent of a parachute. When they do, many refer to a practice actually been tested using an RCT, and half refer to an outcome less important than survival.…”
Section: Lack Of a Counterfactualmentioning
confidence: 99%
“…126‐130)—the latter arising from complex adaptive dynamics . In particular, statistics do not prove causality (and by inference “truth”), regardless weather or not the data are arrived from randomized controlled trials of their meta‐analysis . As far back as 1964, Austin Bradford Hill pointed to the fact that to establish causation requires a “plurality of reasoning strategies”—strength of association between variables, consistency of results between studies, specificity of variables, temporality, biological gradient, plausibility, coherence, experimental evidence, and analogy …”
Section: What Counts As Evidencementioning
confidence: 99%
“…The recent sacking of Peter Gøtzsche from the Cochrane Collaboration Board raised strong responses from either side of the debate and has—as has been suggested—done irreparable damage to the organization. The issues at the heart of this event are that of priorities—maintaining the reputation of the organization or vigorously debating the merits of scientific approaches to find answers to complex problems …”
mentioning
confidence: 99%